Handbook of Dietary Phytochemicals 2020
DOI: 10.1007/978-981-13-1745-3_17-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Monoterpenoids

Abstract: A great number of foods, vegetables, fruits, and beverages contain various types of monoterpenoids and their related compounds. This chapter summarizes the distribution of monoterpenoids in dietary foods, vegetables, fruits, beverages, and processed foods, and their biological activity, effects, and application to our health, as well as metabolic pathways of several monoterpenoids in mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the present study, GC-MS analysis revealed the presence of monoterpenoids p-menth-1-en-9-ol and 1,8-cineole as the dominant compounds in the hydrosol (Table 1). Oxygenated monoterpenes have been previously described as compounds with anticancer activity [59]. Moteki et al [60] reported the cytotoxic activity of 1,8-cineole in leukemia cancer cells.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…In the present study, GC-MS analysis revealed the presence of monoterpenoids p-menth-1-en-9-ol and 1,8-cineole as the dominant compounds in the hydrosol (Table 1). Oxygenated monoterpenes have been previously described as compounds with anticancer activity [59]. Moteki et al [60] reported the cytotoxic activity of 1,8-cineole in leukemia cancer cells.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…Several Nepeta species have traditionally been used as diuretic, diaphoretic, antitussive, antibacterial, antifungal, antispasmodic, antiasthmatic, febrifuge, sedative, spice and herbal tea, as well as food and food supplements, an ingredient of vegetable soup, traditional foods, and used for colds, flu, and bronchitis. Nepetalactones are characteristic monoterpenes for some Napeta species as discussed in the dietary monoterpenoids (Asakawa 2021); however, a number of this species produced different diterpenoids, mainly abietanes and pimaranes (Yilmaz et al 2016).…”
Section: Nepeta (Lamiaceae)mentioning
confidence: 99%
“…Each crude extract including some diterpenes possesses a number of different biological and pharmacological activities. The most frequently recognized activities of diterpenoids are antimicrobial, antifungal, anti-inflammatory, antioxidant, and cytotoxic effects as seen in monoterpenoids (Asakawa 2021).…”
Section: Biological and Pharmacological Activity Of Dietary Diterpenoids And Their Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation